Effects of packet size on FEC performance - Almomani, Omar; Hassan, Suhaidi; Awang Nor, Shahrudin (Universiti Utara Malaysia, 2008)
Packet loss can have a destructive effect on the reconstructed video which makes the presentation displeasing to human eyes. with the availability of Forward Error Correction (FEC), the error of packet losses in streaming applications for both video and audio data can be better managed and controlled.. Different FEC packet sizes can cause variation in packet loss and packet loss ratio. Selecting appropriate packet size is important. In this paper we examine how the FEC packet size effects on the packet loss and packet loss ratio. Ns2 simulator is used to evaluate FEC packet size and find optimal FEC packet size.